Plan de negocios para la implementación de un concesionario de vehículos chinos, cantón Quevedo, año 2014 - Solórzano Segovia, Elsa María (2015)
This research titled "Business Plan for the implementation of a Chinese car dealer, Quevedo Canton, 2014", has the following objectives: to perform a market study to determine the acceptance of a Vehicle Dealer in Canton Chinese Quevedo, make a financial technical and economic study to determine the viability of the company and design a marketing plan that allows implement the strategies of the company. This research project was based through theories and concepts of other authors who have done research that deal with the subject matter, whether books, magazines, brochures, scientific papers, theses, among others. For the development of this research methods, techniques and types they were used that helped them get the conclusions and recommendations of the investigation. The results obtained reflected the following: market research made to the economically active population Quevedo Canton showed that 76.96% if they would like a Vehicle Dealer Chinese thought, this is because the considered low cost, quality and modern, because that can be purchased at any time a vehicle of their choice, technical study, which was to establish the exact location and characteristics to launch the activities of Chinese Vehicle Dealer, financial study showed the project will be economically profitable, since a net profit $458.895,04 in the first year will be obtained as to the cost benefit ratio, it will be $2,22, indicating that for every dollar invested will reach a gain of $1,22 ctvs. to continue to invest, according to….